ChemInform Abstract: Application of CuAAC for the Covalent Immobilization of Homogeneous Catalysts. Issue 19 (13th May 2014) - Fernandes, Antony E.; Jonas, Alain M.; Riant, Olivier
Abstract Review: [101 refs.